Studies on Changes in Soil Properties in Termites (Odontotarmes obesus) Gallaries Developed on Different Tree Species - Singh, S. B.; Singh, A. K.; Tdtav, N. G. (Indian Forester, 1982)
Termite gall aries of Odontotermis obesus collected from the stems of different aged some living forest species showed lower calcium and higher available nitrogen, phosphorus and potash than the soil samples of the area. In general, available nitrogen, pllosphoros and potash were found in the order of termite's gallaries collected from the stem of Boswellia serrata > Madhuca indica> Acacia catechu> Bucchania lanzen > Shorea robusta> Seccopetallum tomentosa > Diospyros melanoxylon.